2020
DOI: 10.56454/qowp3595
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and Planting Geometry Effects on Cotton (Gossypium hirsutum L.) Yield and Water Use

Abstract: Addressing the challenges of dwindling groundwater resources and ever-increasing demands for water necessitate enhancing water use efficiency (WUE) in irrigated agriculture. In a 2-year study, we examined the effects of different levels of irrigation and PG on lint yield and WUE of furrow irrigated cotton in a Dundee silt loam in the Mississippi Delta. The main plots were three irrigation regimes: irrigating every furrow (FI), alternate furrow (HI), and no irrigation (RF) and subplots were two planting geometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…No differences were observed among SR and TR plantings for CO 2 assimilation rate. The TR pattern recorded a 23% increased plant population per unit area over the SR system, which probably has contributed to a 15% lint yield advantage in spite of similar assimilate rates (Pinnamaneni et al, 2020a ). Like soybean, the CO 2 assimilation rate plateaued under light saturation conditions at 1500 μmol m −2 s −1 in cotton.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…No differences were observed among SR and TR plantings for CO 2 assimilation rate. The TR pattern recorded a 23% increased plant population per unit area over the SR system, which probably has contributed to a 15% lint yield advantage in spite of similar assimilate rates (Pinnamaneni et al, 2020a ). Like soybean, the CO 2 assimilation rate plateaued under light saturation conditions at 1500 μmol m −2 s −1 in cotton.…”
Section: Resultsmentioning
confidence: 99%
“…This is probably due to differences in canopy characteristics as cotton was demonstrated to change canopy architecture vis a vis row spacing, cultivar differences, and plant stand establishment. It has been demonstrated that narrow-row and twin-row cotton have a higher leaf area index, which contributes to higher CO 2 assimilation (Heitholt et al, 1992 ; Pettigrew, 2015 ; Pinnamaneni et al, 2020a ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations